Impact of Company Complexity and Investor Behavior on Key Audit Matters: Academic Literature Review - Setiapraptadi, Muhammad Rezky; Nugrahanti, Trinandari Prasetya (Eastasouth Institute, 2025)
In the context of accounting and auditing, the term “key audit matters” refers to key issues that are of primary concern to auditors in conducting an audit. In today’s complex and dynamic business world, companies often operate in an environment full of challenges, risks and uncertainties. This study uses the following keywords: “Key Audit Matters”, “Complexity” and “Investor Behavior”. The search databases used are Google Scholar and Web of Science. We investigate studies that have examined the impact of KAM disclosure on (1) Corporate Complexity, and (2) investor behavior and market reaction. The purpose of this paper is to provide an overview of the existing literature and to summarize the preliminary findings and implications of 8 studies. Key Audit Matters have an effect on investor response and Corporate Complexity leads to increased disclosure in key audit matters.